2018
DOI: 10.4066/biomedicalresearch.29-17-3364
|View full text |Cite
|
Sign up to set email alerts
|

MPV and PDW as inflammatory indicators in chronic otitis media with effusion

Abstract: Objectives: Chronic Otitis Media with Effusion (COME) is a clinical condition characterized by an effusion in the tympanic cavity. In this retrospective study, we aimed to compare the MPV and PDW value of patients with chronic otitis media with effusion (COMA) to those in healthy subjects as an inflammatory indicator. Materials and methods: Demographic features: age, race and gender and laboratory parameters; White Blood Cell count (WBC), Red Blood Cell count (RBC), Hemoglobin (Hb), Hematocrit (Hct), Platelets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…19 Discrepancies in MPV value still being found in recent studies. 18 Our study did not show increased MPV value parallel with severity of obesity, although PDW show a positive trend.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…19 Discrepancies in MPV value still being found in recent studies. 18 Our study did not show increased MPV value parallel with severity of obesity, although PDW show a positive trend.…”
Section: Discussioncontrasting
confidence: 61%
“…17 A high PDW levels found to be caused by swelling, destruction, immaturity, and high reactivity of platelets. 18 Another study reported that MPV and PDW concentrations were significantly higher in the obese group than in the normal weight control group. 19 In obese individuals, although the mechanism underlying the increase was unclear, procoagulant status may have been induced by adipocytokines such as leptin, adiponectin, resistin, and PAI.…”
Section: Discussionmentioning
confidence: 97%